Exploring the relationships between colour and consumer choices. - Liew, Pei Ling. (2008)
The study wants to find out if there is any relationship between colour and consumer choices in the Asian context. A survey was conducted and the results were as follows: Blue is the favourite colour of most Singaporeans. Blue is also the colour that is most frequently associated with packaging of shampoo and snack food. It is also found that there is not one specific colour which can describe a particular personality. Singaporeans are found to be value-conscious consumers who display similar behaviour as other Asian middle class consumers.